Fibroblast-derived EGF ligand neuregulin 1 induces fetal-like reprogramming of the intestinal epithelium without supporting tumorigenic growth - Lemmetyinen Toni T.; Viitala Emma W.; Wartiovaara Linnea; Kaprio Tuomas; Hagström Jaana; Haglund Caj; Katajisto Pekka; Wang Timothy C.; Domeǹech-Moreno Eva; Ollila Saara (Company of Biologists Ltd, 2025)
Growth factors secreted by stromal fibroblasts regulate the intestinal epithelium. Stroma-derived epidermal growth factor (EGF) family ligands are implicated in epithelial regeneration and tumorigenesis, but their specific contributions and associated mechanisms remain unclear. Here, we use primary intestinal organoids modeling homeostatic, injured and tumorigenic epithelia to assess how the fibroblast-derived EGF family ligands neuregulin 1 (NRG1) and epiregulin (EREG) regulate the intestinal epithelium. NRG1 was expressed exclusively in the stroma, robustly increased crypt budding and protected intestinal epithelial organoids from radiation-induced damage. NRG1 also induced regenerative features in the epithelium, including a fetal-like transcriptome, suppression of the Lgr5+ stem cell pool and remodeling of the epithelial actin cytoskeleton. Intriguingly, unlike EGF and EREG, NRG1 failed to support the growth of pre-tumorigenic intestinal organoids lacking the tumor suppressor Apc, commonly mutated in human colorectal cancer (CRC). Interestingly, high expression of stromal NRG1 was associated with improved survival in CRC cohorts, suggesting a tumor-suppressive function. Our results highlight the power of stromal NRG1 in transcriptional reprogramming and protection of the intestinal epithelium from radiation injury without promoting tumorigenesis. © 2023. Published by The Company of Biologists Ltd.
Author keywords
Colorectal cancer; EGF; EREG; Intestinal regeneration; NRG1